Integrasi Teknologi Digital dalam Pendidikan Agama Katolik : Tantangan dan Peluang - Desi Purwaningsih; Tanzila Rahmi; Vicky Agus Arwanda (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This article examines the potential for integrating digital technologies into the teaching of Catholic religious education. The study analyzes data from interviews with 20 Catholic religious teachers in secondary schools, which indicate that digital platforms can enhance teaching effectiveness and student engagement. However, challenges such as the digital divide and limited teacher training are also identified. This article provides practical guidance for overcoming these barriers and leveraging technology to support the mission of evangelization.